Structural Parallelism in Surah ’Abasa: A Study in Grammatical and Semantic Balances - Tounani , Zakaria (Journal of Science and Knowledge Horizons, 2025)
This research presents an analytical study of syntactic parallelism in Surah ’Abasa, focusing on the grammatical and semantic balances that enhance meaning and reveal the Qur’an’s rhetorical miracle. The research provides an analytical examination of practical examples from the surah, such as the parallelism between "he frowned and turned away" and "he might purify himself" and "be reminded," to illustrate how parallelism enhances meaning and strengthens impact. The study recommends expanding this research to other surahs and integrating grammar and rhetoric for a deeper understanding of the Qur’an’s inimitability